Bangladesh, India and Pakistan : international relations and regional tensions in South Asia - Jacques, Kathryn, 1957- (Basingstoke : Palgrave, 2000)
"The book provides a broad, analytical study of Bangladeshs relationship with India and Pakistan between 1975 and 1990. This period was largely one of military rule in Bangladesh, spanning the regimes of Ziaur Rahman (1975-81) and Hussain Muhammad Ershad (1982-90). Bangladeshs role in South Asian international relations has tended to be overlooked or underestimated. Biased and stereotypical views also abound where Bangladesh is concerned, partly due to the prevalence of bias and censorship found in the contemporary media."--BOOK JACKET.
Pt. I. Overview. 1. General Influences on Bangladeshs Foreign Policy -- Pt. II. Regional Influences on Bangladesh-India Relations, 1975-90. 2. 1975-81: Indo-Pakistani Rivalry and Indian Party Politics. 3. 1982-4: A New Beginning or the Darkest Hour? 4. 1985-90: The New Era of Regional Amity and Cooperation -- Pt. III. Domestic Influences on Bangladesh-India Relations, 1975-90. 5. 1975-81: Military Ascendancy in Bangladesh. 6. 1982-90: Political Manoeuvres and Ethnic Violence -- Pt. IV. Bangladesh-Pakistan Relations, 1975-90. 7. 1975-81: Catalysts and Convergences of Interest. 8. 1982-90: A Maturing of Relations?
Includes bibliographical references (p. 216-236) and index.
Keywords: Bangladesh -- Foreign relations -- India; India -- Foreign relations -- Bangladesh; Bangladesh -- Foreign relations -- Pakistan; Pakistan -- Foreign relations -- Bangladesh; South Asia -- Politics and government